The Langkawi island market potential for extreme outdoor sports tourism / Khor Poy Hua, Zul Arif Asrar Zulkefli and Khong Chiu - Khor, Poy Hua; Asrar Zulkefl, Zul Arif; Lim, Khong Chiu (UiTM Cawangan Kedah, 2022)
Today, the idea of sporting activities bears a resemblance to the symbol of a postmodern sports which are also identified as adrenaline rushing sports. Many younger individuals are turning away from the more traditional activities and participating in these "next-generation" activities. Tourist motivation is crucial for host destinations to identify the preference of extreme outdoor sports as it can improve the brand of destination and its engagement with tourist satisfaction and loyalty. This study focuses on the factors of perceived quality, destination image, and perceived value that motivate tourists to select Langkawi as an extreme sports tourism destination. Questionnaires were distributed to 384 extreme sports tourists. Findings shown that extreme sports tourists focus primarily on the perceived quality component in selecting Langkawi Island as their sports destination. They also take into consideration the factors related to destination image and perceived value. Results of Independent Sample t-Test revealed that the male tourists put in extra thought on the quality of merchandise and the quality of tourism product in deciding Langkawi Island as their tourism destination. Furthermore, the male tourists believed that Langkawi Island is a good destination to kill their loneliness. It is advisable for future researchers to focus on other socio-demographic variables for a better understanding of tourist's decision making in selection of extreme sports tourism destinations. These findings could be of reference to the related organisations of sports tourism industry and to the academic field of study in extreme sports tourism.